Study guides

☆☆

Q: 8z - 7 equals 3z - 7 plus 5z?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

8x + 5z - 4x + 3z + 6 = 8x - 4x + 5z + 3z - 6 = 4x + 8z - 6

well, this is pretty easy, just look at it logically:2x - 2y + 5z - 2x - y + 3zwhen you are trying to simplify a formula, your best practice would be to always begin with "organizing" the numbers, in this case it would become:2x - 2x -2y - y + 5z +3zwhen you organize it, it becomes clear what you need to do; first you get rid of the "opposing" values which cancel each other out, in this case the 2x:2x - 2x -2y - y + 5z +3z = -2y - y + 5z + 3zWhen two numbers have the exact same values but one is positive and the other is negative, their result is always zero, so you can simply erase them. In the opposite, when both of them are positive or both of them are negative, then they add up to each other:-2y - y + 5z +3z = -3y + 8z OR 8z - 3yFor this one, I don't think it can be simplified further, 8z - 3y is its' simplest form.

-8z + 12 = 12 - 4z-8z +4z + 12 = 12 - 4z +4z-4z + 12 -12 = 12 -12-4z / -4 = 0 / -4z = 0:)

I assume you mean... 8Z^2 - 64 = 0 8Z^2 = 64 Z^2 = 8 Z = sqrt(8) ( which can be factored and expressed.... ) Z = 2sqrt(2)

8z²

Related questions

-8z + 5z = -3z

8x + 5z - 4x + 3z + 6 = 8x - 4x + 5z + 3z - 6 = 4x + 8z - 6

Add together like terms: 8z-3y

Mid-point: (3z+z)/2, (2z+8z)/2 = (2z, 5z) Slope: (8z-2z)/(3z-z) = 6z/2z = 3 Perpendicular slope: -1/3 Equation: y -5z = -1/3(x -2z) => y = -1/3x+2z/3+5z => y = -1/3x+17z/3 General form of the bisector equation: x+3y-17z = 0

Expand: 8z-4-5z Collect like terms: 3z-4

well, this is pretty easy, just look at it logically:2x - 2y + 5z - 2x - y + 3zwhen you are trying to simplify a formula, your best practice would be to always begin with "organizing" the numbers, in this case it would become:2x - 2x -2y - y + 5z +3zwhen you organize it, it becomes clear what you need to do; first you get rid of the "opposing" values which cancel each other out, in this case the 2x:2x - 2x -2y - y + 5z +3z = -2y - y + 5z + 3zWhen two numbers have the exact same values but one is positive and the other is negative, their result is always zero, so you can simply erase them. In the opposite, when both of them are positive or both of them are negative, then they add up to each other:-2y - y + 5z +3z = -3y + 8z OR 8z - 3yFor this one, I don't think it can be simplified further, 8z - 3y is its' simplest form.

z = -2

2z+6z+24=0 8z+24=0 8z= -24 z= - 3

Z=z

By including its plus or minus signs

-4x + 3y + 3z = -209-6x - y - 8z = -209-9x + 4y - 7z = -418Make a simple equation from elimination.-4x + 3y + 3z = -6x- y - 8z2x + 4y + 11z = 0-4x + 3y + 3z = -2094x + 8y + 22z = 011y + 25z = -209Make another simple equation.-36x - 6y - 48z = -1254-36x + 16y - 28z = -1672-22y - 20z = 418Solve for "z" with the 2 simple equations and then subsitute in simple equations for the solution of "y".22y + 50z = -418-22y - 20z = 41830z = 0z = 011y + 25(0) = -209y = -19Subsitute "y" and "z" and solve for "x".-6x + 19 = -209-6x = -228x = 38(38, -19, 0).

10x + 2y + 8z - 5x + 4z - 4y = 10x - 5x + 2y - 4y + 8z + 4z = (10 - 5)x + (2 - 4)y + (8 + 4)z = 5x - 2y + 12z

People also asked